Norm Uncertainty and Voluntary Payments in the Field - Feldhaus, Christoph; Sobotta, Tassilo; Werner, Peter (Management Science, 2019)
We investigate behavioral reactions toward exogenous changes of implicit norm-relevant information in a natural field setting where customers are free to choose if and how much to pay for a service. Customers’ voluntary payments are significantly affected by subtle information cues: cues that signal a high rather than a low payment norm increase payments by some 27%. Consistent with the conjecture that this effect is in large part driven by customers’ uncertainty about the actual norm, responses are mitigated when explicit norm-relevant information is provided. Additional treatments suggest that the reactions to the cues are not driven by mere saliency but by the information deduced from the cues in the presence of uncertainty. Data are available at https://doi.org/10.1287/mnsc.2017.2937 . This paper was accepted by Uri Gneezy, behavioral economics.